Agroecological analysis of winter wheat yield and it’s dynamics in the Dnipropetrovsk region (period 1966–2016) - O. V. Zhukov; T. O. Pelina (Agrology, 2018)
This article reveals the spatial and temporal patterns of winter wheat yield dynamics in Dnipropetrovsk region and assesses the role of agro–ecological and agroeconomic factors in their formation. The crop data is from the State Statistics Service of Ukraine. The data on yield of winter wheat in the period of 1966–2016, in average per year in administrative districts of Dnipropetrovsk region, are analyzed. The obtained data indicate that the average yields of winter wheat in the Dnipropetrovsk region range from 24.28 CWT/ha to 34.41 CWT/ha. The smallest inter–year variability of yield is characteristic for the Petrikivskyi region (CV = 22.41%), and the highest is for Sofievsky (CV = 31.15%). As a result of the analysis of the main components of winter wheat, the variability of the three main components was revealed, which together account for 84.05% of the total variability of yield. Major component 1 explains 78.18% of total variability. This indicates a general change in synchronous yields in the studied area, since all considered variables have high load values on the main component 1. The administrative districts, that form a belt located in the direction from the North East to the South West region, have a most coordinated the variance, which reflected by the principal component 1. Major component 2 explains 5.87% of the yield variability. This principal component is sensitive to yield opposite dynamics of central and south-western regions on the one hand and the eastern and northern regions – on the other. Cluster analysis of administrative districts was conducted based on the dynamics of winter wheat crop yields, which resulted in the discovery of four clusters. Clusters are geographically defined administrative districts, forming spatially bound areas. A similar temporal dynamics of winter wheat yields as a result of the interaction of endogenous and exogenous environmental factors is the main principle of the discovery of such environmentally homogeneous territories. The spatial distribution of the main components indicates a continuous nature, but their overlay allows us to extract the spatially discrete units that we have identified agroecological zones. Each zone is characterized by a certain character and dynamics of production capacities and has an invariant scheme of response to various climatic, ecological and agroeconomic factors.